Vitamin D Receptor Gene Polymorphism: An Important Predictor of Arthritis Development. (18th March 2019) - Mukhtar, Maryam; Sheikh, Nadeem; Suqaina, Saira Kainat; Batool, Andleeb; Fatima, Naz; Mehmood, Rabia; Nazir, Sabeen
Abstract : Vitamin D is an anti-inflammatory molecule and has a role in prevention of arthritis development. Biologically active form 1, 25(OH)2 D3 of vitamin D can only exert its action after binding its definite vitamin D receptor encoded by VDR gene. VDR gene polymorphism leads to dysfunctioning of 1, 25(OH)2 D3 ultimately disease onset. The purpose of current study was to evaluate the effect of vitamin D level and VDR gene polymorphism on rheumatoid arthritis and osteoarthritis. Blood samples were collected from case and control after taking written consent. Serum was separated and vitamin D level as determined from each sample by ELISA. DNA was extracted from each blood sample and amplified by using gene specific primers. Genotyping was performed by Sangers sequencing and PCR-RFLP technique. It was found that vitamin D level was not significantly different among patients and controls. The rs10735810, rs1544410, rs7975232, and rs731236 were associated with the onset of arthritis at both allelic and genotypic level (p < 0.01). Nucleotide change on rs10735810 site leads to change of tryptophan with arginine. The frequencies of haplotype CGAT, CGGA, CGGT, CTAA, CTAT, TGAA, TGAT, TGGA, and TTGA were higher in patients and act as risk factors of RA onset, whereas haplotypes CGAT, CGAT, CGGT, CTGA, TGAT, TGGA, TTAA, and TTGA were associated with OA onset. In conclusion, serum vitamin D level may be normal among arthritis patients but polymorphism on VDR gene restricts vitamin D to perform its anti-inflammatory function by altering the 1, 25(OH)2 D3 binding sites.